Mechanistic investigation into particulate matter formation during air and oxyfuel combustion of formulated water-soluble fractions of bio-oil - Feng, C.; Wu, Hongwei (Combustion Institute, 2018)
© 2018. This paper reports a systematic study on the formation of particulate matter with diameter of <10 µm (i.e., PM10) during the combustion of two formulated water-soluble fractions (FWSFs) of bio-oil in a drop-tube-furnace (DTF) at 1400 °C under air or oxyfuel (30%O2/70%CO2) conditions. FWSF-1 was an organic-free calcium chloride solution with a calcium concentration similar to that in the bio-oil. FWSF-2 was formulated from the compositions of major organics in bio-oil WSF, doped with calcium chloride at the same concentration. The results suggest that similar to bio-oil combustion, the FWSF combustion produces mainly particulate matter with diameter of between 0.1 and 10 µm (i.e., PM0.1-10). Since there are no combustibles in the organic-free FWSF-1, the PM is produced via droplet evaporation followed by crystallization, fusion and further reactions to form CaO (in air or argon) or partially CaCO3(under oxyfuel condition). With the addition of organics, FWSF-2 combustion produces PM10shifting to smaller sizes due to extensive break up of droplets via microexplosion. Sprays with larger droplet size produce PM10with increased sizes. The results show that upon cooling CaO produced during combustion in air can react with HCl gas to form CaCl2in PM0.1. The predicted PSDs of PM10based on the assumption that one droplet produces one PM particle is considerably larger than experimentally-measured PSDs of PM10during the combustion of FWSFs, confirming that breakup of spray droplets takes place and such breakup is extensive for FWSF-2 when organics are present in the fuel.